(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Agricultural commerce in South Sulawesi Province, especially the products, is mostly operated in form of informal relation between commerce practitioners. Due to imperfect condition in the market, social capital thrives and becomes bread and butter in operating entire market system. This article belongs to social system analysis on agricultural product commerce in South Sulawesi as an effort to comprehend the condition constituting background of the operating market system. Writing contents are fetched from previous studies on commerce of various agricultural product commodities as well trader behavior.